Preparation method of water-based nano magnesium hydroxide dispersion and nano magnesium hydroxide / PVA (Polyvinyl Alcohol) composite film

By introducing ionic liquids during the preparation of magnesium hydroxide to form nanomagnesium hydroxide dispersion, the problems of poor dispersion in water and poor dispersion and compatibility during PVA recombination are solved, and high dispersion is achieved and good flame retardant properties.

CN119410030APending Publication Date: 2025-02-11ZHENGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411593923.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The dispersion formed by magnesium hydroxide in water has poor dispersion and poor dispersion and compatibility when PVA recombination.

Method used

By introducing an ionic liquid and mixing it with a magnesium source, a uniform and stable complex solution was formed, and homogeneous precipitation reaction was carried out with the hydroxide to obtain a nanomagnesium hydroxide dispersion. Ionic liquid crystallizes through coordination reaction, hydrogen bonding and electrostatic action to form small-sized nanomagnesium hydroxide particles to prevent their aggregation in an aqueous environment.

Benefits of technology

The dispersion and stability of magnesium hydroxide in an aqueous environment are improved, and its dispersion and compatibility when compounded with PVA are enhanced, thereby improving the flame retardant performance of the composite film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410030A_ABST
    Figure CN119410030A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of magnesium compounds, and particularly relates to a preparation method of a water-based nano magnesium hydroxide dispersion and a nano magnesium hydroxide / PVA composite film. The preparation method of the water-based nano magnesium hydroxide dispersion comprises the following steps: mixing an ionic liquid and a magnesium source to prepare a complex solution, adding hydroxide into the complex solution, carrying out homogeneous precipitation reaction to obtain turbid liquid, centrifuging the turbid liquid, washing, and dispersing in water to obtain the nano magnesium hydroxide dispersion, the ionic liquid is selected from one of 1-butyl-3-methylimidazolium acrylate, 1-butyl-3-methylimidazolium glycine salt and N-methylimidazolium acrylate, and the ionic liquid is selected from one of 1-butyl-3-methylimidazolium glycine salt and N-methylimidazolium acrylate. Acrylic acid and glycine anions of the ionic liquid are more easily coordinated with metal, the effects of controlled release of magnesium ions and space blocking are achieved, reactive crystallization is regulated and controlled through the coordination reaction, the hydrogen-bond interaction and the electrostatic interaction of the ionic liquid, small-size magnesium hydroxide is induced to be formed, and aggregation of the small-size magnesium hydroxide in a water-based environment can be prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium compounds, and in particular to a method for preparing an aqueous nano magnesium hydroxide dispersion and a nano magnesium hydroxide / PVA composite film. Background Art

[0002] As an important inorganic halogen-free smoke suppression flame retardant, magnesium hydroxide has better thermal stability, smoke suppression performance, flame retardancy and environmental protection. Therefore, magnesium hydroxide has been widely used in halogen-free flame retardant (HFFR) polymer materials. However, due to the wide particle size distribution of magnesium hydroxide, strong surface polarity, and easy aggregation into secondary particles, it is difficult to disperse in the organic matrix when used as a flame retardant, resulting in a significant decrease in the mechanical properties of the composite. Therefore, in order to improve the dispersibility of nano-magnesium hydroxide in composite materials, it is necessary to modify the surface of magnesium hydroxide to prepare a stable and well-dispersed nano-magnesium hydroxide dispersion.

[0003] The Chinese patent with the authorization announcement number CN103911021B, which was authorized on June 1, 2016, discloses a transparent magnesium hydroxide liquid phase dispersion, a preparation method and an application thereof, wherein a magnesium salt solution and an alkali solution are mixed to obtain a reaction solution, a surfactant is added to the reaction solution for modification, and a filter cake obtained after standing, filtering and washing is dispersed in a solvent to obtain a magnesium hydroxide liquid phase dispersion. The surfactant is selected from hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, alkane silicon, oleic acid, stearic acid, etc., and a dispersion is obtained by surface modification and dispersion, which well solves the problems of poor dispersibility and compatibility of nano magnesium hydroxide in applications.

[0004] However, the transparent magnesium hydroxide liquid phase dispersion prepared by the above method still has the problem of poor dispersibility. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing an aqueous nano magnesium hydroxide dispersion, so as to solve the problem of poor dispersibility of the magnesium hydroxide dispersion formed by magnesium hydroxide in water.

[0006] The second object of the present invention is to provide a nano magnesium hydroxide / PVA composite film to solve the problems of poor dispersibility and compatibility when the existing magnesium hydroxide dispersion and PVA are composited.

[0007] In order to solve the above technical problems, the technical solution of the preparation method of the aqueous nano magnesium hydroxide dispersion of the present invention is: A method for preparing an aqueous nano magnesium hydroxide dispersion comprises the following steps: mixing an ionic liquid and a magnesium source to prepare a complex solution, adding a hydroxide to the complex solution for a homogeneous precipitation reaction to obtain a suspension, washing the suspension after centrifugation, and then dispersing it in water to obtain a nano magnesium hydroxide dispersion, wherein the ionic liquid is selected from one of 1-butyl-3-methylimidazole acrylate, 1-butyl-3-methylimidazole glycine and N-methylimidazole acrylate.

[0008] The invention improves the prior art and provides a method for preparing a nano magnesium hydroxide dispersion. The introduced ionic liquid first reacts with magnesium ions to obtain a uniform and stable complex solution, and then reacts with hydroxide to undergo a homogeneous precipitation reaction. Acrylic acid anions and glycine anions in the ionic liquid are more easily coordinated with metals, thereby playing a role in controlling the release of magnesium ions and spatial barrier, and effectively dispersing nano magnesium hydroxide particles. The ionic liquid is used as a multi-effect regulating agent, and the nano magnesium hydroxide is prepared by in-situ modification using a homogeneous reaction method by utilizing the ionic liquid. The coordination reaction, hydrogen bonding action, and electrostatic action of the ionic liquid regulate the reaction crystallization, thereby inducing the formation of small-sized nano magnesium hydroxide particles and preventing the aggregation of the nano magnesium hydroxide particles in an aqueous environment. The optimized ionic liquid structure is selected to strengthen the multi-scale synergistic effect, improve the dispersion stability of the magnesium hydroxide nano dispersion, improve the dispersibility of the nano magnesium hydroxide in an aqueous environment, and further improve the dispersibility and compatibility when compounded with PVA.

[0009] In order to further prevent the aggregation of nano magnesium hydroxide particles and improve the coordination modification efficiency of the ionic liquid, preferably, the molar ratio of the ionic liquid, the magnesium ions in the magnesium source and the hydroxide ions in the hydroxide is (0.1-2): (2-2.5): (5-6.25).

[0010] In order to further improve the precipitation efficiency of the homogeneous reaction, preferably, the temperature of the homogeneous precipitation reaction is 25-60° C., and the time of the homogeneous precipitation reaction is 1-2 h.

[0011] In order to further improve the dispersibility of nano-magnesium hydroxide in the solvent, preferably, ultrasonic treatment is used during the dispersion, the power of the ultrasonic treatment is 30-900W, and the time of the ultrasonic treatment is 10-30min.

[0012] In order to further improve the coordination efficiency and precipitation efficiency, preferably, the magnesium source is selected from one of magnesium sulfate, magnesium chloride and magnesium nitrate, and the hydroxide is selected from one of sodium hydroxide and potassium hydroxide.

[0013] The technical solution of the nano magnesium hydroxide / PVA composite film of the present invention is: A nano magnesium hydroxide / PVA composite film is obtained by mixing an aqueous nano magnesium hydroxide dispersion prepared by the method for preparing an aqueous nano magnesium hydroxide dispersion and a PVA solution and then molding the mixture.

[0014] The nano magnesium hydroxide / PVA composite film provided by the present invention is prepared by mixing an aqueous nano magnesium hydroxide dispersion with a PVA solution, which can greatly improve the dispersibility of nano magnesium hydroxide in a PVA matrix, thereby improving the flame retardant properties of the composite film without destroying its mechanical properties.

[0015] In order to further improve the flame retardant properties of the polyvinyl alcohol composite film, preferably, the molar amount of nano magnesium hydroxide corresponding to every 5-10 g of polyvinyl alcohol is 0.0008-0.008 mol.

[0016] In order to further improve the preparation efficiency of the PVA composite film, preferably, the forming is to transfer the mixed solution obtained by mixing the nano magnesium hydroxide dispersion and the PVA solution into a mold for drying. The nano magnesium hydroxide / PVA composite film prepared by the present invention does not destroy the transparency of polyvinyl alcohol, and at the same time gives polyvinyl alcohol good flame retardant properties.

[0017] In order to further improve the dispersibility of nano-magnesium hydroxide in polyvinyl alcohol, preferably, the PVA solution is obtained by dissolving PVA in water at 85-95°C, and the mixing is to continue adding the nano-magnesium hydroxide dispersion into the PVA solution at 85-95°C.

[0018] In order to further improve the preparation efficiency of the polyvinyl alcohol composite film, preferably, the mixed solution is evaporated to 25-30% of the original volume before being transferred to the mold for drying, and the drying is first allowed to stand at room temperature for 1-1.5 days, and then vacuum dried at 60-70°C for 2-3 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The particle size distribution and zeta potential test result diagram of the nano magnesium hydroxide dispersion obtained by the preparation method of Example 1 of the present invention; Figure 2 The particle size distribution and zeta potential test result diagram of the nano magnesium hydroxide dispersion obtained by the preparation method of Example 2 of the present invention; Figure 3 The particle size distribution and zeta potential test result diagram of the nano magnesium hydroxide dispersion obtained by the preparation method of Example 3 of the present invention; Figure 4 This is a flow chart of preparing a nano magnesium hydroxide / polyvinyl alcohol composite film according to Example 4 of the present invention; Figure 5This is a graph showing the particle size distribution and zeta potential test results of the nano-magnesium hydroxide dispersion obtained by the preparation method of Comparative Example 1 of the present invention; Figure 6 This is a SEM image of the nano-magnesium hydroxide / polyvinyl alcohol composite film after combustion according to Example 4 of the present invention; Figure 7 This is a SEM image of the nano-magnesium hydroxide / polyvinyl alcohol composite film after combustion according to Example 5 of the present invention; Figure 8 This is a SEM image of the nano-magnesium hydroxide / polyvinyl alcohol composite film after combustion according to Example 6 of the present invention; Fig. 9 This is a SEM image of the nano-magnesium hydroxide / polyvinyl alcohol composite film of Comparative Example 2 of the present invention after combustion.

[0020] Fig.10 This is the DMA curve of nano-magnesium hydroxide / polyvinyl alcohol composite film. DETAILED DESCRIPTION

[0021] The technical concept of the preparation method of the aqueous nano magnesium hydroxide dispersion of the present invention is as follows: The prior art uses a surfactant to modify the surface of a magnesium hydroxide reaction liquid obtained by reacting a magnesium salt with an alkali solution, so as to improve the dispersibility and stability of nano magnesium hydroxide; while the present invention introduces an ionic liquid in the preparation process, so that anions in the ionic liquid are more easily coordinated with magnesium ions to form a uniform and stable complex solution, which plays a role in controlling the release and spatial barrier of magnesium ions. Through the coordination reaction, hydrogen bonding and electrostatic action of the ionic liquid to regulate the reaction crystallization, small-sized nano magnesium hydroxide particles are induced to form and the aggregation of nano magnesium hydroxide particles in an aqueous environment can be prevented, so as to obtain an aqueous nano magnesium hydroxide dispersion solution with good dispersibility.

[0022] The structural formulas of the three ionic liquids are as follows:

[0023] Among them, a is 1-butyl-3-methylimidazolium acrylate; b is 1-butyl-3-methylimidazolium glycine; and c is N-methylimidazolium acrylate.

[0024] In a specific embodiment, the complex solution is obtained by adding an ionic liquid aqueous solution dropwise to a magnesium source aqueous solution and then stirring, the concentration of the ionic liquid aqueous solution is 0.02-0.4 mol / L, and the concentration of magnesium ions in the magnesium source aqueous solution is 0.4-0.5 mol / L.

[0025] In a specific embodiment, the suspension is obtained by dropwise adding a hydroxide aqueous solution into a complex solution for a homogeneous precipitation reaction, and the concentration of hydroxide ions in the hydroxide aqueous solution is 0.5-0.625 mol / L.

[0026] In a specific embodiment, the ionic liquid aqueous solution, the magnesium source aqueous solution and the hydroxide aqueous solution are obtained by dissolving the ionic liquid, the magnesium source and the hydroxide in water, respectively.

[0027] In a specific implementation manner, the molar concentration of the nano-magnesium hydroxide dispersion is 0.01-0.1 mol / L, and the mass concentration of the polyvinyl alcohol solution is 50-100 g / L.

[0028] In a specific embodiment, the evaporation is to evaporate the mixed solution at 85-95°C.

[0029] The implementation manner of the present invention is further described below in conjunction with specific examples.

[0030] 1. Specific embodiment of the method for preparing the aqueous nano-magnesium hydroxide dispersion of the present invention Example 1 The preparation method of the aqueous nano magnesium hydroxide dispersion of the present embodiment is as follows: At room temperature, magnesium sulfate heptahydrate, sodium hydroxide, and 1-butyl-3-methylimidazole acrylate were weighed separately, and the three were dissolved in water to obtain magnesium sulfate heptahydrate aqueous solution, sodium hydroxide aqueous solution, and 1-butyl-3-methylimidazole acrylate aqueous solution, and the volumes were fixed to 50 ml, 100 ml, and 50 ml, respectively, and the concentrations of the three aqueous solutions were controlled to be 0.4 mol / L, 0.5 mol / L, and 0.02 mol / L, respectively.

[0031] The 1-butyl-3-methylimidazole acrylate aqueous solution was dropped into the magnesium sulfate heptahydrate aqueous solution and stirred evenly to form a uniform complex solution. Then, the sodium hydroxide solution was added to the complex solution at 50° C. to carry out a homogeneous precipitation reaction for 1.85 hours to obtain a nano magnesium hydroxide suspension.

[0032] The suspension was centrifuged at a speed of 3000 r / min, and after removing the supernatant, it was washed with water and alcohol, and 80 ml of water was added. The power of the cell ultrasonic disruptor was adjusted to 60 W. After ultrasonication for 10 minutes, a uniform aqueous nano-magnesium hydroxide dispersion was obtained.

[0033] Particle size distribution of aqueous nano-magnesium hydroxide dispersion ( Figure 1 a) and zeta potential ( Figure 1 b) The test results are shown in Figure Figure 1 As shown. Figure 1 It can be seen that the average particle size of nano magnesium hydroxide is maintained at 93.96nm, reaching the nanoscale, and its average zeta potential is -23.37mV, which is relatively stable and not easy to settle.

[0034] Example 2 The preparation method of the aqueous nano magnesium hydroxide dispersion of the present embodiment is as follows: At room temperature, magnesium sulfate heptahydrate, sodium hydroxide, and 1-butyl-3-methylimidazolyl glycinate were weighed respectively, and the three were dissolved in water to obtain magnesium sulfate heptahydrate aqueous solution, sodium hydroxide aqueous solution, and 1-butyl-3-methylimidazolyl glycinate aqueous solution, and the volumes were fixed to 50 ml, 100 ml, and 50 ml, respectively, and the concentrations of the three aqueous solutions were controlled to be 0.5 mol / L, 0.625 mol / L, and 0.04 mol / L, respectively.

[0035] The aqueous solution of 1-butyl-3-methylimidazolium glycine salt is dropped into the aqueous solution of magnesium sulfate heptahydrate, and stirred evenly to form a uniform complex solution. Then, sodium hydroxide solution is added to the complex solution at 60°C to carry out a homogeneous precipitation reaction of 1.25 to obtain a nano magnesium hydroxide suspension.

[0036] The suspension was centrifuged at a speed of 3000 r / min, and after removing the supernatant, it was washed with water and alcohol, and 80 ml of water was added. The power of the cell ultrasonic disruptor was adjusted to 30 W. After ultrasonication for 10 minutes, a uniform aqueous nano-magnesium hydroxide dispersion was obtained.

[0037] Particle size distribution of aqueous nano-magnesium hydroxide dispersion ( Figure 2 a) and zeta potential ( Figure 2 b) The test results are shown in Figure Figure 2 As shown. Figure 2 It can be seen that the average particle size of nano magnesium hydroxide is maintained at 81.68nm, reaching the nanoscale, and its average zeta potential is -31.85mV, which is extremely stable and not easy to settle.

[0038] Example 3 The preparation method of the aqueous nano magnesium hydroxide dispersion of the present embodiment is as follows: At room temperature, magnesium sulfate heptahydrate, sodium hydroxide, and N-methylimidazole acrylate were weighed separately, and the three were dissolved in water to obtain magnesium sulfate heptahydrate aqueous solution, sodium hydroxide aqueous solution, and N-methylimidazole acrylate aqueous solution, and the volumes were fixed to 50 ml, 100 ml, and 50 ml, respectively, and the concentrations of the three aqueous solutions were controlled to be 0.4 mol / L, 0.6 mol / L, and 0.04 mol / L, respectively.

[0039] The N-methylimidazole acrylate aqueous solution is dropped into the magnesium sulfate heptahydrate aqueous solution and stirred evenly to form a uniform complex solution. Then, the sodium hydroxide solution is added to the complex solution at 25°C to carry out a homogeneous precipitation reaction for 1.25 hours to obtain a nano magnesium hydroxide suspension.

[0040] The suspension was centrifuged at a speed of 3000 r / min, and after removing the supernatant, it was washed with water and alcohol, and 80 ml of water was added. The power of the cell ultrasonic disruptor was adjusted to 900 W. After ultrasonication for 10 minutes, a uniform aqueous nano-magnesium hydroxide dispersion was obtained.

[0041] Particle size distribution of aqueous nano-magnesium hydroxide dispersion ( Figure 3 a) and zeta potential ( Figure 3 b) The test results are shown in Figure Figure 3 As shown. Figure 3 It can be seen that the average particle size of nano magnesium hydroxide is maintained at 154.5 nm, reaching the nanoscale, and its average zeta potential is -17.24 mV. It has general stability and is not easy to settle.

[0042] 2. Specific embodiments of the nano-magnesium hydroxide / PVA composite film of the present invention Example 4 The nano magnesium hydroxide / PVA composite film of this embodiment is prepared by the following method: The preparation flow chart of nano magnesium hydroxide / PVA composite film is as follows Figure 4 As shown, 10 g of polyvinyl alcohol (PVA, analytical grade, purchased from Shanghai McLean Biochemical Technology Co., Ltd.) was mixed with 90 ml of water, heated in a water bath at 95°C to form a transparent PVA aqueous solution, and then 80 ml of nano-magnesium hydroxide (MH) dispersion obtained by the preparation method of Example 1 was added to obtain a mixed solution. The mixed solution was further heated at 95°C to evaporate to 50 ml, and then the mixed solution was transferred to a mold, allowed to stand at room temperature for 1 day, and then transferred to a vacuum drying oven at 60°C for drying for 2 hours to obtain a PVA / MH composite film.

[0043] Example 5 The nano magnesium hydroxide / PVA composite film of this embodiment is prepared by the following method: 10 g of polyvinyl alcohol (PVA) was mixed with 90 ml of water, and heated in a water bath at 90° C. to form a transparent PVA aqueous solution. 80 ml of nano-magnesium hydroxide (MH) dispersion obtained by the preparation method of Example 2 was added to obtain a mixed solution. The mixed solution was further heated at 90° C. to evaporate to 50 ml. The mixed solution was then transferred to a mold, allowed to stand at room temperature for 1 day, and then transferred to a vacuum drying oven at 60° C. for drying for 2 hours to obtain a PVA / MH composite film.

[0044] Example 6 The nano magnesium hydroxide / PVA composite film of this embodiment is prepared by the following method: 10 g of polyvinyl alcohol (PVA) was mixed with 90 ml of water, and heated in a water bath at 90° C. to form a transparent PVA aqueous solution. 80 ml of nano-magnesium hydroxide (MH) dispersion obtained by the preparation method of Example 3 was added to obtain a mixed solution. The mixed solution was further heated at 90° C. to evaporate to 50 ml. The mixed solution was then transferred to a mold, allowed to stand at room temperature for 1 day, and then transferred to a vacuum drying oven at 60° C. for drying for 2 hours to obtain a PVA / MH composite film.

[0045] 3. Comparison Comparative Example 1 The preparation method of the aqueous nano-magnesium hydroxide dispersion in this comparative example does not involve ionic liquid, and the specific preparation method is as follows: At room temperature, magnesium sulfate heptahydrate and sodium hydroxide were weighed separately, and the two were dissolved in water to obtain magnesium sulfate heptahydrate aqueous solution and sodium hydroxide aqueous solution, and the volumes were fixed to 50 ml and 100 ml respectively, and the concentrations of the two aqueous solutions were controlled to be 0.4 mol / L and 0.5 mol / L respectively.

[0046] Place the magnesium sulfate heptahydrate aqueous solution in a three-necked flask preheated in a constant temperature water bath at 25°C, heat and stir to make the solution temperature uniform, the stirring speed is 400r / min, and at the same time, place the sodium hydroxide aqueous solution in a 25°C water bath for preheating. After preheating, add the sodium hydroxide aqueous solution dropwise into the three-necked flask, continue stirring, control the dropping time to 15min, and the stirring speed is 400r / min. After the dropwise addition is completed, continue the homogeneous precipitation reaction at this temperature for 1.0h to obtain a suspension.

[0047] The suspension was centrifuged at a speed of 3000 r / min, and after removing the supernatant, it was washed with water and alcohol, and 80 ml of water was added. The power of the cell ultrasonic disruptor was adjusted to 90 W. After ultrasonication for 10 minutes, a uniform aqueous nano-magnesium hydroxide dispersion was obtained.

[0048] Particle size distribution of aqueous nano-magnesium hydroxide dispersion ( Figure 5 a) and zeta potential ( Figure 5 b) The test results are shown in Figure Figure 5 As shown. Figure 5 It can be seen that the average particle size of nano magnesium hydroxide is maintained at 256.0 nm, reaching the nanoscale, and its average zeta potential is -9.69 mV, with poor stability and easy sedimentation.

[0049] Comparative Example 2 The nano magnesium hydroxide / PVA composite film of this comparative example is prepared by the following method: 10 g of polyvinyl alcohol (PVA) was mixed with 90 ml of water, and heated in a water bath at 90° C. to form a transparent PVA aqueous solution. 80 ml of nano-magnesium hydroxide (MH) dispersion obtained by the preparation method of Comparative Example 1 was added to obtain a mixed solution. The mixed solution was further heated at 90° C. to evaporate to 50 ml. The mixed solution was then transferred to a mold, allowed to stand at room temperature for 1 day, and then transferred to a vacuum drying oven at 60° C. for drying for 2 hours to obtain a UN-PVA / MH composite film.

[0050] IV. Experimental Examples Experimental Example 1 This experimental example characterizes the morphology of the nano-magnesium hydroxide / PVA composite film after combustion. The SEM images of the nano-magnesium hydroxide / PVA composite film of Examples 4-6 after combustion are shown in Figures 1 and 2. Figure 6-8 As shown, the SEM image of the nano magnesium hydroxide / PVA composite film of Comparative Example 2 after combustion is as follows Fig. 9 As shown. Figure 6 It can be seen that after the composite film of Example 4 is burned, the carbon layer is extremely dense, with only wrinkles on its surface and no obvious pores. The magnesium oxide decomposed after the magnesium hydroxide is burned inside the material is evenly distributed, playing a flame retardant role. Figure 7 It can be seen that many holes appear on the surface of the composite film of Example 5 after combustion, and the magnesium oxide particles decomposed by the magnesium hydroxide inside the material after combustion are closely arranged and evenly distributed in size, giving full play to the flame retardant effect; Figure 8 It can be seen that after burning, there are obvious cracks and holes on the surface of the composite film of Example 6, which can fully play the flame retardant effect. Fig. 9 It can be seen that there are no obvious bubbles and small holes on the surface of the material after the UN-PVA / MH composite film is burned. When it is magnified, it is found that there are only a few small particles on the surface, which are the decomposed MgO.

[0051] Experimental Example 2 This experimental example tests the combustion performance of nano magnesium hydroxide / PVA composite film. Micro combustion calorimeter (MCC) is an effective method to evaluate the combustion performance of materials. MCC is used to test and analyze the two key indicators of the prepared nano magnesium hydroxide / PVA composite film, heat release capacity (HRC) and maximum heat release rate (PHRR). The horizontal burning rate of the composite film is tested using the national standard GB / T 2408-2021 to evaluate its thermal stability and flame retardancy. The test results are shown in Table 1.

[0052] Table 1 Performance test results of nano magnesium hydroxide / PVA composite film

[0053] From the test results in Table 1, it can be seen that the two key MCC data heat release capacity (HRC) and maximum heat release rate (PHRR) of the PVA / MH composite film (Examples 4-6) provided by the present invention are greatly reduced compared with the UN-PVA / MH composite film (Comparative Example 2) obtained without introducing ionic liquid, indicating that the aqueous nano-magnesium hydroxide dispersion of the present invention plays a good role in improving the flame retardant properties of the material.

[0054] Among them, the HRC of the PVA / MH composite film of Example 4 decreased from 454.8J / g∙k to 210.2J / g∙k, and the PHRR decreased from 460.7w / g to 208.6w / g; in terms of thermal stability and flame retardancy, PVA / MH showed better flame retardancy, with a horizontal burning rate of 466.21mm / min, which was 9.0% lower than that of the UN-PVA / MH film. The HRC of the PVA / MH composite film of Example 5 decreased from 454.8J / g∙k to 196.6J / g∙k, and the PHRR decreased from 460.7w / g to 198.9w / g; in terms of thermal stability and flame retardancy, the horizontal burning rate was 324.28mm / min, which was 36.7% lower than that of the UN-PVA / MH film. The HRC of the PVA / MH composite film of Example 6 decreased from 454.8 J / g∙k to 365.4 J / g∙k, and the PHRR decreased from 460.7 W / g to 369.7 W / g; in terms of thermal stability and flame retardancy, PVA / MH exhibited better flame retardant properties, with a horizontal burning rate of 399.4 mm / min, which was 22.0% lower than that of the UN-PVA / MH film.

[0055] Experimental Example 3 Dynamic mechanical properties (DMA) testing is one of the most effective and widely used methods for studying the mechanical properties of viscoelastic polymers. In this experimental example, DMA testing was performed on nano-magnesium hydroxide / polyvinyl alcohol composite films (Comparative Example 2, Example 4, Example 5 and Example 6). The storage modulus curves are shown in Figure 2. Fig.10 shown.

[0056] from Fig.10It can be seen that the storage modulus of all film samples decreases with the increase of temperature, that is, as the temperature increases, the rigidity of the material decreases. The storage modulus of the UN-PVA / MH film of Comparative Example 2 is smaller, the strength is lower, and it is easy to deform; while the storage modulus of the PVA / MH composite film of Example 4, Example 5 and Example 6 becomes larger and the strength is higher, which proves that the introduction of ionic liquid during the preparation of magnesium hydroxide can improve the dispersibility and compatibility of nano magnesium hydroxide and PVA when compounded, and after testing, all three can be bent at room temperature and will not break easily. At the same time, with the increase of temperature, the mechanical properties of the PVA / MH composite film of Example 5 are less improved, while improving the rigidity of the material, the softness of the film material is maintained, and its storage modulus decreases more slowly, and the thermal stability is also better.

[0057] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an aqueous nano-magnesium hydroxide dispersion, characterized in that: The following steps are involved: An ionic liquid and a magnesium source are mixed to prepare a complex solution, a hydroxide is added to the complex solution for a homogeneous precipitation reaction to obtain a suspension, the suspension is centrifuged and then washed, and then dispersed in water to obtain a nano magnesium hydroxide dispersion, wherein the ionic liquid is selected from one of 1-butyl-3-methylimidazole acrylate, 1-butyl-3-methylimidazole glycine and N-methylimidazole acrylate.

2. The method for preparing an aqueous nano-magnesium hydroxide dispersion according to claim 1, wherein: The molar ratio of the ionic liquid, the magnesium ions in the magnesium source and the hydroxide ions in the hydroxide is (0.1-2): (2-2.5): (5-6.25).

3. The method for preparing an aqueous nano-magnesium hydroxide dispersion according to claim 1, wherein: The temperature of the homogeneous precipitation reaction is 25-60° C., and the time of the homogeneous precipitation reaction is 1-2 hours.

4. The method for preparing an aqueous nano-magnesium hydroxide dispersion according to claim 1, wherein: The dispersion is carried out by ultrasonic treatment, the power of the ultrasonic treatment is 30-900W, and the time of the ultrasonic treatment is 10-30min.

5. The method for preparing an aqueous nano-magnesium hydroxide dispersion according to claim 1, wherein: The magnesium source is selected from one of magnesium sulfate, magnesium chloride and magnesium nitrate, and the hydroxide is selected from one of sodium hydroxide and potassium hydroxide.

6. A nano magnesium hydroxide / PVA composite film, characterized in that: The nano-magnesium hydroxide / PVA composite film is obtained by mixing an aqueous nano-magnesium hydroxide dispersion prepared by the method for preparing an aqueous nano-magnesium hydroxide dispersion according to any one of claims 1 to 5 and a PVA solution and then molding the mixture.

7. The nano magnesium hydroxide / PVA composite film according to claim 6, characterized in that: The molar amount of nano magnesium hydroxide corresponding to every 5-10 g of polyvinyl alcohol is 0.0008-0.008 mol.

8. The nano magnesium hydroxide / PVA composite film according to claim 6, characterized in that: The molding process is to transfer the mixed solution obtained by mixing the nano magnesium hydroxide dispersion and the PVA solution into a mold for drying.

9. The nano magnesium hydroxide / PVA composite film according to claim 6 or 8, characterized in that: The PVA solution is obtained by dissolving PVA in water at 85-95° C., and the mixing is to continue adding the nano-magnesium hydroxide dispersion into the PVA solution at 85-95° C.

10. The nano magnesium hydroxide / PVA composite film according to claim 8, characterized in that: The mixed solution is transferred to a mold for drying and then evaporated to 25-30% of the original volume. The drying is performed by first standing at room temperature for 1-1.5 days and then vacuum drying at 60-70° C. for 2-3 hours.

Citation Information

Patent Citations

  • A kind of transparent magnesium hydroxide liquid phase dispersion and its preparation method and application

    CN103911021B